An Investigation on the Takeoff Performance of a Light Amphibious Airplane - Chinvorarat, Sinchai; Watjatrakul, Boonchai; Nimdum, Pongsak; Sangpet, Teerawat; Vallikul, Pumyos (New Approaches in Engineering Research Vol. 13, 2021)
This article presents the results of a performance evaluation of a light amphibious aircraft during takeoff from the water's surface. The aircraft is part of a Thai-built small amphibious airplane series with a bi-wing layout. The concept design intends to create a short takeoff and landing (STOL) amphibious aircraft. MATLAB@ is used to demonstrate and solve a mathematical model that collaborates with many complex factors. The water-drag resistance of the aircraft is calculated using standard seaplane hull NASA technical information, which improves the model's accuracy during takeoff. The simulation shows that the seaplane can takeoff from calm water in 26 seconds at a speed of 54 KCAS and a distance of about 890 feet with an AOA of 10 degrees.